Expression of human adenosine deaminase in nonhuman primates after retrovirus-mediated gene transfer (The Rockefeller University Press, 1987)
Primate bone marrow cells were infected with a retroviral vector carrying the genes for human adenosine deaminase (h-ADA) and bacterial neomycin resistance (neor). The infected cells were infused back into the lethally irradiated donor animals. Several monkeys fully reconstituted and were shown to express the h-ADA and neor genes at low levels in their recirculating hematopoietic cells for short periods of time.